Evaluation of Fertilizer Potential of Different K Compounds Prepared Utilizing Sea Bittern as Feed Stock - Trivedi, Khanjan; Kubavat, Denish; Ghara, Krishna K.; Kumar, Ranjeet; Trivedi, Hardik; Anand, K. G. Vijay; Maiti, Pratyush; Ghosh, Arup (Frontiers in Plant Science, 2017)
Aim: Many countries import potassic fertilizers due to dearth of K-mineral deposits. Therefore processes to obtain K-nutrient sources from sea bittern were developed by our Institute. The present investigation evaluated the fertilizer potential of three different sea bittern-derived (SBD) potassium forms developed viz., potassium schoenite, potassium nitrate and potassium ammonium sulphate on maize productivity in two cropping seasons. Methods: The pot and field experiments consisted of four treatments, wherein the three K forms were applied at the recommended rate of 40 kg K2O ha-1 and were compared with commercially used sulphate of potash. The effect of these fertilizers on different parameters of plant and soil were evaluated. Results: The application of SBD-potassic fertilizers led to enhancement in growth, productivity and quality of maize which related well with higher photosynthesis, nutrient uptake and soil quality parameters. On an average all the three forms of sea bittern-derived potash enhanced yield of maize over control by 22.3% and 23.8%, respectively, in pot and field trials. The best performance was under SBD-KNO3, which also recorded the highest benefit: cost ratio of 1.76. Conclusion: The K-fertilizers derived from sea-bittern—a waste product of salt industry—can thus be economically used to improve crop production sustainably.